1891
DOI: 10.1055/s-0029-1206570
|View full text |Cite
|
Sign up to set email alerts
|

Die Wirksamkeit kleiner Tuberkulindosen gegen Lungenschwindsucht

Abstract: Wciterc 1Iitthei1llllgdll über die mît dem koeh'sehell Heilmittel C%VOHllCllCll Erfahrungen. XIX. Aus dem städtischen Krankenhause Moabit in Berlin. Die Wirksamkeit kleiner Tuberkulind.osen gegen Lungenschwindsucht. Von Paul (iuttmann und P. Ehrlieh.1) Vor einiger Zeit haben wir in dieser Wochenschrift (No. 10) eine Mittheiluug gemacht über die Behandlung der Lungentuberculose mit sehr kleinen Dosen Tuberkulins. Schon damals konnten wir erklären, dass bei dieser minimal beginnenden und sehr allmählich aufsteig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1892
1892
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…[160,161] Methylene blue, which was used against malaria in the past, [195,196] is today the standard medication against methemoglobinemia and against ifosfamid-associated neurotoxicity. [178] Methylene blue has a number of desirable properties as an antimalarial drug.…”
Section: Drug Binding In the Central Cavitymentioning
confidence: 99%
“…[160,161] Methylene blue, which was used against malaria in the past, [195,196] is today the standard medication against methemoglobinemia and against ifosfamid-associated neurotoxicity. [178] Methylene blue has a number of desirable properties as an antimalarial drug.…”
Section: Drug Binding In the Central Cavitymentioning
confidence: 99%
“…Thus, most of the observed reaction describes the breakdown of the MDS. Methylene Blue in the Reductive and Oxidative Half-reaction-PfGR is the only verified enzymic target of the antimalarial dye methylene blue (13,19,20). The addition of 1-3 eq of inhibitor in the oxidative half-reaction did not affect the kinetic characteristics of the reaction.…”
Section: Spectralmentioning
confidence: 99%
“…50,51) Vennerstrom and co-workers reexamined the in vitro antimalarial potencies of xanthene, azine, oxazine, and thiazine dyes and reported that several of these dyes displayed strong in vitro activity against drug resistant P. falciparum. 47) In connection with our working DLC hypothesis, we examined the antimalarial potencies of several readily available dyes.…”
Section: )mentioning
confidence: 99%